2022
DOI: 10.3390/healthcare10101991
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Oil Pulling for Improving Oral Health: A Meta-Analysis

Abstract: Objective: The effect of oil pulling on oral health has not yet been fully demonstrated. Therefore, we performed a meta-analysis to investigate the effect of oil pulling on oral health. Methods: We searched PubMed, the Cochrane Library, and the EMBASE database, limiting the search to human patients and articles written in English and published before 31 July 2022. We included randomized controlled trials (RCTs) comparing the effect of oil pulling on improving dental health and oral hygiene. The outcomes of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recent research has demonstrated that sesame oil and sunflower oil can effectively mitigate the development of plaque-induced gingivitis [9]. The root of Sesame (Sesamum indicum) is known to contain chlorosesamone, a compound that exhibits antifungal properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has demonstrated that sesame oil and sunflower oil can effectively mitigate the development of plaque-induced gingivitis [9]. The root of Sesame (Sesamum indicum) is known to contain chlorosesamone, a compound that exhibits antifungal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Coconut oil (CO) and sesame oil (SO) have historically been recognised as the preferred oils for the practise of OPT [ 8 ]. Recent research has demonstrated that sesame oil and sunflower oil can effectively mitigate the development of plaque-induced gingivitis [ 9 ]. The root of Sesame ( Sesamum indicum ) is known to contain chlorosesamone, a compound that exhibits antifungal properties.…”
Section: Introductionmentioning
confidence: 99%